2019
DOI: 10.3390/app9051012
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Design of a Tower Type SCR-deNOx Facility for a 1000 MW Coal-Fired Power Plant Based on CFD Simulation and FMT Validation

Abstract: Selective catalytic reduction (SCR) is one of the most efficient methods to reduce NOx emissions from coal-fired power plants. This paper deals with an optimal design tower type SCR-deNOx facility for a 1000 MW coal-fired power plant. Combined with computational fluid dynamics (CFD), the configuration of the baffles geometry was studied with spatial constraints. Flow field was regulated at the ammonia injection grid (AIG) with the dual aim of reducing difficulties in implementing the non-uniformed ammonia (NH3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In an SCR, the design of the mixer affects the performance, and Mehdi et al studied the optimal design to reduce NOx using a numerical investigation [3]. Zeng et al used CFD simulation to study the optimal design of a towertype SCR [4], and the method of analyzing the gas flow of the SCR using numerical analysis is being used with its accuracy verified.…”
Section: Introductionmentioning
confidence: 99%
“…In an SCR, the design of the mixer affects the performance, and Mehdi et al studied the optimal design to reduce NOx using a numerical investigation [3]. Zeng et al used CFD simulation to study the optimal design of a towertype SCR [4], and the method of analyzing the gas flow of the SCR using numerical analysis is being used with its accuracy verified.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have used CFD methods to calculate the distribution, formation and reduction of nitrogen oxides [21]. Many works also model sub-systems of power boilers, such as SCR reactors [10,22] or dedusting systems. In [23], the mixing of the flue gas stream with primary air was modeled to increase the flue gas temperature before the SCR installation.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen oxides (NOx) are common air pollutants in industrial exhaust gas. The massive emission of NOx is responsible for the formation of smog, acid rain and photochemical smog, which causes great harm to the environment and human health [1,2]. According to the relative policy, the NOx emission is limited to 100 mg•Nm -3 for the pulverized coal boiler in China [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have explored how to optimize the flow field in the SCR system. Zeng et al [1] found that installing small-sized baffles upstream of the facility was helpful to improve the uniformity of flow field. Yu et al [6] and Zhong et al [7] paid their attention to the effect of gas-solid flow on catalyst erosion.…”
Section: Introductionmentioning
confidence: 99%